Relevance and possibilities of body condition scoring in beef cattle breeding - Domokos, Zoltán; Szentléleki, Andrea; Tőzsér, János (Animal welfare, Ethology and Housing Systems (AWETH), 2011)
The aim of our study is to highlight the relevance of body condition scoring in beef cattle farming, by showing the effect of body condition on reproductive performance as well as the different scoring systems. Spreading the body condition scoring of beef cattle is would be necessary in Hungary, since this is an effective management tool for monitoring the nutritional program throughout the year so that the pregnant cows can obtain the optimal condition at calving. Regular control of herd condition and consequential grouping, possibly feed supplementation could considerably enhance the productive efficiency.
Keywords: body condition scoring; beef cattle breeding; suckling cow; reproduction; efficiency